Association between blood lead levels and blood pressures in a non-smoking healthy Korean population. Issue 1103 (23rd August 2016) - Lee, Kyu Rae; Ko, Ki Dong; Hwang, In Cheol; Suh, Heuy Sun; Kim, Kyoung Kon
ABSTRACT: Objective: The Korea National Health and Nutrition Examination Survey (KNHANES) has been performed every 3 years in Korea to help prevent cardiovascular mortality in the general population. Previous studies showed an association between blood lead levels and cardiovascular mortality. In order to assess the relationship between blood lead concentration and blood pressure in the healthy general population, we investigated whether blood lead levels were related to blood pressure in a non-smoking healthy population without any known medical diseases in the 2013 KNHANES. Methods: 896 (mean age 40.55±13.83 years; body mass index 23.06±3.33 kg/m 2 ) subjects who had no known diseases were included among 8018 subjects. Exclusion criteria were: hypertension, diabetes, hyperlipidaemia, cerebrovascular events, renal insufficiency, liver cirrhosis, thyroid dysfunction, any cardiovascular or renal disease, and any malignancy. Blood pressures were measured three times by sphygmomanometers, 5 min apart. Blood pressures were then expressed as the average between the second and third values. Height, weight, waist circumferences and blood pressure, as well as total cholesterol, high density lipoprotein cholesterol, triglycerides, low density lipoprotein cholesterol, aspartate aminotransferase (AST), alanine aminotransferase (ALT), white blood cell count and blood lead levels were measured. In addition, dietary components were analysed by 24 hour recall. Results: The association between log blood lead levels and systolic/diastolic pressure was stronger after it was controlled for age, sex, education, body mass index (BMI), waist circumference and fasting plasma glucose (FPG) (p=0.048, 0.002). Furthermore, the association between log blood lead levels and systolic pressure (p=0.048) and diastolic pressure (p=0.002) was more evident when controlled for age, sex, education, BMI, waist circumference, FPG, AST and ALT. Conclusions: Blood lead levels are significant determinants of systolic and diastolic blood pressure in a healthy Korean population, irrespective of sociodemographic factors and metabolic derangements.